Membangun Budaya Kreatif Melalui Seni Batik di Yayasan Cinta Yatim & Dhuafa, Pisangan Barat, Kec.Cirendeu, Kota Tangerang Selatan - Susan Ary Ayu Anjani; Shela Amelia AKhap; Muhammad Farhan Nugraha; Muammar Khadafi; Ahmad Fajar Mahendra; Dian Islami; Adriansyah Harun; Rochman Rayhan; Reza Setiansa; Sa’diah El Adawiyah (Lembaga Pengembangan Kinerja Dosen, 2024)
Abstract. Education plays an important role in shaping a bright and sustainable future, with creative and fun learning as the key to creating an inspiring learning environment. This article examines the event